2014
DOI: 10.1038/ncomms4724
|View full text |Cite
|
Sign up to set email alerts
|

Protein conformational dynamics dictate the binding affinity for a ligand

Abstract: Interactions between a protein and a ligand are essential to all biological processes. Binding and dissociation are the two fundamental steps of ligand-protein interactions, and determine the binding affinity. Intrinsic conformational dynamics of proteins have been suggested to play crucial roles in ligand binding and dissociation. Here, we demonstrate how protein dynamics dictate the binding and dissociation of a ligand through a single-molecule kinetic analysis for a series of maltose-binding protein mutants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
118
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(134 citation statements)
references
References 38 publications
12
118
0
Order By: Relevance
“…To verify proper reconstitution, we observed the time duration of fluorescence bursts in a confocal microscope with McjD in detergent and in proteoliposomes and found the expected increase for proteoliposomes to about 10–20 ms (Fig EV3A) compared to ~1 ms for McjD in detergent micelles. These values are similar to reported ones for other diffusing liposome systems (Seo et al , 2014). Finally, we verified random insertion (inside‐out and inside‐in) of McjD into the proteoliposomes with a ratio of ca.…”
Section: Resultssupporting
confidence: 92%
“…To verify proper reconstitution, we observed the time duration of fluorescence bursts in a confocal microscope with McjD in detergent and in proteoliposomes and found the expected increase for proteoliposomes to about 10–20 ms (Fig EV3A) compared to ~1 ms for McjD in detergent micelles. These values are similar to reported ones for other diffusing liposome systems (Seo et al , 2014). Finally, we verified random insertion (inside‐out and inside‐in) of McjD into the proteoliposomes with a ratio of ca.…”
Section: Resultssupporting
confidence: 92%
“…It has been frequently observed that enzymes in their free unliganded state sample 3D conformations that consist of those visited in the presence of the ligand (7). Differences in intrinsic conformational dynamics in the wild type and the mutant maltose-binding proteins have been shown to be related to association and dissociation of ligand and thereby to affect dissociation constants (8). Enzyme dynamics in Cyclophilin A (CypA), a peptidyl prolyl cis-trans isomerase, have been demonstrated to occur on the same millisecond timescale as the catalytic turnover (9).…”
mentioning
confidence: 99%
“…The ability of the pocket to close around different ligands can contribute to specificity (5). Switching to the inactive state of the receptor dramatically increases the dissociation rate, so pocket dynamics controls the residence time of ligands (4,12), and thus the catalytic rate of most enzymes (3). The importance of the inactive state to association rates is less clear; inactive states have been shown have lower (4,12), similar (13), or higher (14) association rates relative to the active state, and the functional importance of the differences is unclear.…”
mentioning
confidence: 99%